2010
DOI: 10.5251/ajsir.2010.1.3.435.438
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus infection in voluntary blood donors in North-Eastern Nigeria

Abstract: The Human immunodeficiency virus infection is known to occur in the general population, and due to their mode of transmission through blood and blood products, it has made the provision of safe blood increasingly difficult, and the screening of blood absolutely necessary. The objective was to determine the sero-prevalence of Human immunodeficiency virus infection among voluntary blood donors. It was a hospital-based cross sectional study. Place of study was the Blood

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 10 publications
3
16
2
Order By: Relevance
“…this is much higher than a similar study done at Lagos, which recorded 4.7% 2 our results were much higher than a report of a similar study done at Yola, Nigeria 2.4% 11 . Some previous reports were higher than ours for instance, a study done at Ibadan Nigeria by Fashola et al 12 reported a prevalence rate of 13.2%, another study done in the South-south region of Nigeria reported 10.6%…”
Section: Tti Neg 82%contrasting
confidence: 56%
“…this is much higher than a similar study done at Lagos, which recorded 4.7% 2 our results were much higher than a report of a similar study done at Yola, Nigeria 2.4% 11 . Some previous reports were higher than ours for instance, a study done at Ibadan Nigeria by Fashola et al 12 reported a prevalence rate of 13.2%, another study done in the South-south region of Nigeria reported 10.6%…”
Section: Tti Neg 82%contrasting
confidence: 56%
“…A number of them have suggested that increasing age is a higher risk to have the disease, probably due to longer exposure to multiple risk factors, [12][13][14] and higher in males than females. 15,16 Although, the sample size is not very large as compared to the report in earlier studies stated, but the results obtained are very important since this is the first study from Calabar, Nigeria, where a high frequency rate has been seen in ELISA method when compared to rapid strip test device. So, there is a great and urgent need for people in this locality and beyond to screen their blood for HBV and it should be screened using the ELISA technique which has been found to be more sensitive and accurate as compared to the rapid test strip device method.…”
Section: Discussionmentioning
confidence: 67%
“…14,15 Following Blumberg's discovery of hepatitis B surface antigen (HBsAg), many attempts have been made to develop several in vitro diagnostic techniques for the detection of this antigen and its homologous antibody, including a wide-range of different serological, immunological and molecular-biological techniques. 16 According to the financial facilities as well as technical feasibility (i.e. trained personnel and the availability of advanced laboratory equipment) one should have the choice to select and apply one or more of these laboratory tests.…”
Section: Introductionmentioning
confidence: 99%
“…Our study noted no correlation between HIV and other infections. A strict selection criteria for blood donors to exclude those with multiple sexual partners is recommended, and all the affected donors should be treated appropriately [35].…”
Section: Discussionmentioning
confidence: 99%